Relationships Between Depression and Stress Factors in Housework and Paid Work Among Japanese Women - Aiko Hoshino; Shigeaki Amano; Kunifumi Suzuki; Mami Suwa (SAGE Publishing, 2016)
Objective/Background: The prevalence of depression in women is two times as much as that in men. However, the rehabilitation programme for return to work for patients with depression in Japan mainly focuses on male individuals. Japanese working women usually have the central role in housework in addition to paid work. Therefore, we hypothesized that Japanese working women with depression need a support programme for housework as well as paid work. The purpose of this study was to investigate the stress factors relevant to the existence of depression, in both paid work and housework, among working women. Methods: This study recruited 35 women with depression and 35 women without depression. We carried out a cross-sectional investigation with two questionnaires having the same structure: The National Institute for Occupational Safety and Health (NIOSH) Generic Job Stress Questionnaire (for paid work) and the NIOSH Generic Housekeeping Labor Stress Questionnaire (for housework). We extracted the stress factors contributing to the existence of depression using logistic regression. Results: Three stress factors were found-two in housework, and one in paid work. In housework, variance in workload and underutilization of abilities were associated with the presence of depression. In paid work, interpersonal conflict was an associated factor. Conclusion: Rehabilitation programmes involving variance in workload and under self-evaluation in housework, and interpersonal conflict in paid work must be adequately addressed to support working women with depression.